2013
DOI: 10.1037/a0031955
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive anatomy of tutor learning: Lessons learned with SimStudent.

Abstract: This article describes an advanced learning technology used to investigate hypotheses about learning by teaching. The proposed technology is an instance of a teachable agent, called SimStudent, that learns skills (e.g., for solving linear equations) from examples and from feedback on performance. SimStudent has been integrated into an online, gamelike environment in which students act as “tutors” and can interactively teach SimStudent by providing it with examples and feedback. We conducted 3 classroom “in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 43 publications
3
48
0
4
Order By: Relevance
“…A variation on reflective theories of learning has been the emergence of systems aimed to help learners learn by getting them to teach the material to be learned to someone else, typically a simulated fellow student such as Betty's Brain (Leelawong and Biswas 2008). The issue of how much this helps a learner to learn has been explored in a series of studies using SimStudent (Matsuda et al 2013). SimStudent is a simulated student that uses machine-learning techniques to build production rules expressing a skill such as solving a simple equation in algebra.…”
Section: Derived From Learning Theorymentioning
confidence: 99%
“…A variation on reflective theories of learning has been the emergence of systems aimed to help learners learn by getting them to teach the material to be learned to someone else, typically a simulated fellow student such as Betty's Brain (Leelawong and Biswas 2008). The issue of how much this helps a learner to learn has been explored in a series of studies using SimStudent (Matsuda et al 2013). SimStudent is a simulated student that uses machine-learning techniques to build production rules expressing a skill such as solving a simple equation in algebra.…”
Section: Derived From Learning Theorymentioning
confidence: 99%
“…Experiment in 2 different places. This study reveals that prior knowledge greatly influenced the learning process [6]. In addition, regression analysis shows that prior knowledge is the dominant facemask affecting post-test results for procedural ability testing.…”
Section: Introductionmentioning
confidence: 79%
“…Investigations of CBLEs have demonstrated that learning can be supported in a wide range of educational domains, from algebra to history (e.g., Anderson, Corbett, Koedinger, & Pelletier, 1995;Beal, Walles, Arroyo, & Woolf, 2007;Matsuda et al, 2013;Poitras, Lajoie, & Hong, 2011;Vanlehn et al, 2005). This body of work elucidates the salient role that technology plays in learning experiences and outcomes.…”
Section: Related Workmentioning
confidence: 94%